Prevalence of Hyperemesis Gravidarum Based on Age, Parity, and Severity - Salsa Bella, Sarah Chaerani; Idris, Syamsul Bahri M.S.; Selomo, Prita Aulia M. (CV. Publikasi Indonesia, 2025)
Hyperemesis gravidarum is a persistent nausea and vomiting which is the main cause of hospitalization after preterm delivery in all the pregnancies. Globally, the prevalence of hyperemesis gravidarum is 12.5% and the prevalence of hyperemesis gravidarum in North Maluku is around 3.66%. To describe the incidence of hyperemesis gravidarum at RSUD Dr. H. Chasan Boesoirie. The type of research is a retrospective descriptive observational approach with a total sampling technique of 94 patients. Data were collected from medical record data according to the inclusion and the exclusion criteria and it is used univariate analysis. Patients at risk for hyperemesis gravidarum based on the age, namely 20-35 years, were 78 patients (84.8%), then based on parity at risk, namely multigravida, 45 patients (48.9%) and based on the degree of severity who were at risk of being affected, namely 59 patients (64.1%). The majority of the pregnant women are affected by hyperemesis gravidarum, namely at the age of 20-35 years, the multigravida parity and the moderate degree.